155 Effect of Forage Inclusion Strategy on Finishing Beef Cattle Performance and Liver Abscesses. (21st September 2022) - Paterson, Tyen J; Penner, Gregory B; Lardner, Bart; Stephens, Emma; Gruninger, Robert J; Yang, WenZhu; Beauchemin, Karen A; McAllister, Tim A; Ribeiro, Gabriel O
Abstract: This study evaluated different strategies of forage inclusion for finishing beef cattle and their impact on performance, carcass quality, and liver abscesses. Steers (n=360, 400±29 kg) were blocked by weight and randomly assigned to one of four treatments (15 steers/pen, 6 pens/treatment) in a complete randomized experiment. Treatments were: 1) positive control (+CON) fed a diet (7.5% forage on a diet DM basis) with tylosin (11 mg/kg); 2) negative control (–CON; control diet without tylosin); 3) a diet where forage concentration decreased (DECR) every 42 d and was static for the last 84 d (forage represented 15%, 9%, 3%, and 3% of DM, respectively) without tylosin; and 4) a diet where forage concentration increased (INCR), the inverse of the DECR without tylosin. There were no differences in initial BW, DMI, and G:F (P≥0.38). The INCR steers had lower ADG (1.63 vs. 1.74 kg, P=0.05), total BW gain (287 vs. 306 kg, P=0.05), and tended to have lower final BW and carcass weight (P=0.07) compared to +CON, with no differences from the other treatments. No differences were observed for carcass dressing percentage, ribeye area, marbling scores, and quality grades (P≥0.41). Backfat thickness and yield score were lower for INCR steers (14.2 mm and 3.42) compared to –CON (16.9 mm and 3.82, P=0.04), while other treatments did not differ. There was no difference for the percentage of steers with liver abscess or severe abscess (A+; P≥0.17). However, the percentage of steers with minor liver abscesses (A) was numerically less for +CON (51.8%) and DECR (51.8%) compared to –CON (62.2%) and INCR (64.3%, P=0.055). This suggests that higher dietary concentrations of forage in the beginning stages of finishing, with a subsequent decline thereafter has the potential to decrease the proportion of minor liver abscesses, similar to the inclusion of tylosin in a high-grain diet, without impacting growth performance or carcass quality.